Financial Constraints and Coping Mechanisms of Barangay Health Workers: A Correlational Study on Savings and Credit Utilization (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Barangay Health Workers (BHWs) play a vital role in delivering primary healthcare services at the community level; however, many continue to experience persistent financial challenges that affect their well-being and capacity to perform their functions effectively. This study examined the financial constraints and coping mechanisms of BHWs in Poblacion, Sta. Cruz, Marinduque, with particular emphasis on savings behavior and credit utilization. Employing a quantitative descriptive–correlational research design, data were collected from 38 BHWs selected through stratified random sampling across five barangays. A researcher-developed questionnaire was used, and data were analyzed using descriptive statistics, Pearson correlation, and the Kruskal–Wallis H test, guided by Financial Strain Theory and Goal Setting Theory. Results revealed that low and irregular honoraria, high out-of-pocket expenses, and limited access to formal financial resources were the primary sources of financial strain among BHWs. A moderate positive relationship was found between financial constraints and coping mechanisms, indicating that increased financial difficulty was associated with greater reliance on adaptive strategies such as borrowing and informal savings. No significant differences were observed in financial constraints when respondents were grouped according to demographic profile, suggesting that financial challenges are structurally driven rather than demographic-specific. The findings support the implementation of inclusive Financial Wellness and Resilience programs, improved access to formal financial services, and strengthened institutional and policy support to enhance the financial stability and quality of life of BHWs. These recommendations contribute to the advancement of Sustainable Development Goals, particularly SDG 1 (No Poverty), SDG 3 (Good Health and Well-being), and SDG 8 (Decent Work and Economic Growth).